Zirconia media, bearing balls and their manufacturing method

By adjusting the chemical composition and microstructure of the ZrO2-Y2O3 system sintered body, the cracks and fragment problems caused by uneven strength of the bead grinding body are solved, and efficient powder grinding and dispersion are achieved, and the high purity of the powder is maintained.

JP7648848B2Active Publication Date: 2025-03-18NIKKATO CORPORATION

Patent Information

Application Number
JP2024517927
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-04-25
Filing Date
2023-04-03
Publication Date
2025-03-18
Estimated Expiration
2043-04-03

AI Technical Summary

Technical Problem

In the prior art, when using a high-speed rotating bead mill for powder grinding and dispersion, the strength of the bead mill is uneven, and cracks and fragments are easily generated due to stress concentration, resulting in a decrease in the purity of the powder and poor grinding effect.

Method used

The ZrO2-Y2O3-type sintered body is used as the bead abrasive body, and its chemical composition and microstructure are controlled to obtain excellent wear resistance and durability. Specific measures include adjusting the molar ratio of Y2O3/ZrO2, adding Al2O3 and controlling the phase composition, and ensuring that the phase diagram and grain size are distributed within a specific range.

Benefits of technology

By optimizing the chemical composition and microstructure of the bead grinding body, the strength consistency and wear resistance of the bead grinding body are significantly improved, cracks and fragment problems caused by uneven strength are avoided, and the high purity of the powder is maintained and the grinding effect is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648848000018
    Figure 0007648848000018
  • Figure 0007648848000019
    Figure 0007648848000019
  • Figure 0007648848000020
    Figure 0007648848000020
Patent Text Reader

Abstract

Provided are a zirconia media having improved wear resistance and durability, zirconia bearing balls, and a manufacturing method thereof. The zirconia media: (a) comprises a ZrO2–Y2O3-based zirconia sintered body, the Y2O3 / ZrO2 molar ratio being in a range of 2.5 / 97.5 to 3.2 / 96.8 inclusive; (b) has a Al2O3 content in a range of 0.1 to 30.0 mass% inclusive; (c) contains 90% by volume or more of tetragonal zirconia; (d) has a relative density of 95% or more; (e) has an average crystal grain size in a range of 0.25 to 0.50 μm inclusive; (f) has a minimum compression load value of Pmin (N)>600×D2.0 (D being the average media diameter); (g) has a Weibull coefficient of crushing load value of 10 or more; and (h) has a media diameter coefficient of variation of less than 6%. 
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to zirconia media, bearing balls, and methods for producing the same. [Background technology]

[0002] In recent years, electronic component materials such as ceramic laminate capacitors have become smaller and more functional. In the manufacture of inorganic powders used as raw materials, importance is attached to pulverization, high dispersion, and high purity. In the pulverization process of such powders, grinding and dispersion processing is carried out by a bead mill using media made of fine inorganic sintered bodies. In the mill, the micro media is processed by stirring at high speed to perform highly efficient grinding and dispersion processing. For this reason, the load given to the media is large, and Y2O3-reinforced zirconia micro media, which has excellent impact resistance and abrasion resistance, is used. Because of their small size, micro media need to be put into the mill in large quantities. If even a small amount of low-strength media is present among the media put in, the high-speed rotation in the mill places a high load on the media, which can easily cause the media to break. If the media breaks and breaks into pieces, the pieces may be crushed and become foreign matter and become mixed into the powder being processed. In addition, depending on the grinding and dispersion conditions, the slurry temperature in the mill may become high, which may cause the media to deteriorate in strength or wear resistance, resulting in the inclusion of foreign matter.

[0003] Patent Document 1 describes a method for dispersing a pigment in a solution, in which the average particle size is 40 to 192 μm and the density is 5.9 g / cm 3 The above discloses the use of zirconia sintered beads having a sphericity of 1.07 or less. However, when powder is pulverized and dispersed using a bead mill, simply suppressing the variations in average particle size, density, and sphericity does not prevent the occurrence of cracks or chips due to stress concentration on the strength of the media or defects present inside the media. In other words, Patent Document 1 does not mention the variations in the strength of the beads, and suppressing the variations in the average particle size, density, and sphericity does not prevent the variations in strength.

[0004] Patent Document 2 discloses a ZrO2-Y2O3-based zirconia sintered body used as a grinding and dispersing medium, in which wear resistance is obtained by controlling the chemical composition and microstructure. It is disclosed that the ZrO2-Y2O3-based zirconia sintered body described in Patent Document 2 has excellent wear resistance when grinding and dispersing hard powders. However, there is no description that adjusting the chemical composition of ZrO2-Y2O3 zirconia sintered compacts suppresses the variation in properties of the entire micro media.When used as a micro media under high load, if the entire micro media does not meet the required strength, there is a risk of cracking or chipping due to stress concentration on the micro media with slightly lower strength.

[0005] Patent Document 3 describes that the average crystal grain size may differ between the center and the surface of the sintered sphere due to the difference in the granulation method of the molded sphere before sintering. It describes that if the average crystal grain size of the sphere is larger near the center than near the surface, wear progresses significantly in the early stages and the amount of impurities mixed in increases dramatically. It describes that if the average crystal grain size of the sphere is smaller near the center than near the surface, the strength decreases significantly because the number of internal voids increases and the voids become the starting point of destruction. Therefore, it is disclosed that the uniformity of the average crystal grain size between the center and the surface of each sphere is adjusted by adjusting the specific surface area and average secondary particle size of the ZrO2 powder used to mold the molded sphere before sintering to a specific range, and further adjusting the chemical composition such as the content of Y2O3, Al2O3, Fe, Ti, etc. to a specific range. However, even if the uniformity of the average crystal particle size inside the sphere and near the surface is adjusted, if the variation in strength of the micro media as a whole is not suppressed, there is a risk of cracks or chips occurring due to stress concentration on the micro media, which has slightly lower strength, when the powder to be processed is crushed and dispersed.

[0006] Patent Document 4 discloses a zirconia sintered body that exhibits excellent wear resistance and durability stably for a long period of time in hot water or a high humidity atmosphere at about 100°C or below 100°C by controlling the molar ratio of Y2O3 and ZrO2, the Al2O3 content, the total SiO2 and TiO2 content, and the average crystal grain size. However, there is no description that the variation in the properties of the entire micro media can be suppressed even if the chemical composition of the ZrO2-Y2O3 zirconia sintered body is adjusted. When used as a micro media under high load, if the entire micro media does not meet the required strength, there is a risk of cracking or chipping due to stress concentration on the micro media with slightly lower strength, as in Patent Document 2, which may lead to a decrease in durability. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 7-155577 [Patent Document 2] JP 2014-205586 A [Patent Document 3] JP 2004-315246 A [Patent Document 4] JP 2004-307339 A Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the present invention is to provide zirconia media and bearing balls which have reduced variations in media shape and mechanical properties and have improved wear resistance and durability, and methods for producing the same. [Means for solving the problem]

[0009] The first aspect of the present invention is (a) a ZrO2-Y2O3-based zirconia sintered body, the Y2O3 / ZrO2 molar ratio being within the range of 2.5 / 97.5 or more and 3.2 / 96.8 or less; (b) the content of Al2O3 is within the range of 0.1 mass% or more and 30.0 mass% or less, (c) containing 90% or more by volume of tetragonal zirconia; (d) the relative density is 95% or more; (e) the average grain size is within the range of 0.25 μm or more and 0.50 μm or less; (f) Measured at a crosshead speed of 0.5 mm / min. Crushing load The minimum weight is Pmin(N)>600×D 2.0 (D is the average media diameter) (g) The Weibull coefficient of the crushing load is 10 or more; (h) the maximum diameter of the media that can be confirmed in an SEM image confirmed using a scanning electron microscope is defined as the media diameter, and the coefficient of variation of the media diameter derived from the average value and standard deviation of the media diameters of 200 media is less than 6%; The zirconia media satisfies the above requirements (a) to (h).

[0010] The second aspect of the present invention is (a) a ZrO2-Y2O3-based zirconia sintered body, the Y2O3 / ZrO2 molar ratio being within the range of 2.5 / 97.5 or more and 3.2 / 96.8 or less; (b) the content of Al2O3 is within the range of 0.1 mass% or more and 30.0 mass% or less, (c) containing 90% or more by volume of tetragonal zirconia; (d) the relative density is 95% or more; (e) the average grain size is within the range of 0.25 μm or more and 0.50 μm or less; (f) Measured at a crosshead speed of 0.5 mm / min. Crushing load The minimum weight is Pmin(N)>600×D 2.0(D is the average media diameter) (g) The Weibull coefficient of the crushing load is 10 or more; (h) the maximum diameter of the media that can be confirmed in an SEM image confirmed using a scanning electron microscope is defined as the media diameter, and the coefficient of variation of the media diameter derived from the average value and standard deviation of the media diameters of 200 media is less than 6%; (x) Fracture toughness is 5.0 MPa m 1 / 2 Beyond (y) A zirconia bearing ball having a bending strength exceeding 1100 MPa and a Weibull modulus of bending strength exceeding 7.

[0011] The third aspect of the present invention is a method for producing a powder of a zirconium or yttrium material, comprising: (p) mixing a zirconium raw material and a yttrium raw material so that the Y2O3 / ZrO2 molar ratio is within a range of 2.5 / 97.5 to 3.2 / 96.8, hydrolyzing the mixture, and calcining the resulting hydrate of zirconium and yttrium at a temperature within a range of 600°C to 1200°C; (q) mixing the Al2O3 powder with the Al2O3 powder so that the Al2O3 content is within the range of 0.1 mass% to 30.0 mass% of the total amount to obtain a mixed powder; (r) The mixed powder is wet-pulverized and / or dispersed to obtain a mixed powder slurry, and the dried powder has a specific surface area of ​​5 m2 as measured by the BET method. 2 / g or more 10m 2 / g or less, (s) wet-pulverizing and / or dispersing the mixed powder slurry so that the average particle size at 50% cumulative frequency in a volume-based particle size distribution measured in accordance with JIS Z8825 by a laser diffraction method is within the range of 0.3 μm to 0.6 μm; (t) preparing a molding powder by drying and sieving the resulting powder obtained by mixing 1 part by mass of the dried powder from the mixed powder slurry with 100 parts by mass of a molding solvent, so that the aggregated powder in the slurry for measuring the aggregated powder average particle size has a cumulative frequency of 50% in a volume-based particle size distribution measured in accordance with JIS Z8825 by a laser diffraction method, within a range of 1 μm or more and 5 μm or less; (u) granulating and molding the molding powder to obtain a molded body; (v) sintering the green body at a temperature in the range of 1250° C. to 1600° C. to obtain a ZrO2-Y2O3-based zirconia sintered body, which is a method for producing zirconia media comprising the sintered body.

[0012] A fourth aspect of the present invention is a method for producing a powder of a zirconium or yttrium composite material, comprising: (p) mixing a zirconium raw material and a yttrium raw material so that the Y2O3 / ZrO2 molar ratio is within a range of 2.5 / 97.5 to 3.2 / 96.8, hydrolyzing the mixture, and calcining the resulting hydrate of zirconium and yttrium at a temperature within a range of 600°C to 1200°C; (q) mixing the Al2O3 powder with the Al2O3 powder so that the Al2O3 content is within the range of 0.1 mass% to 30.0 mass% of the total amount to obtain a mixed powder; (r) The mixed powder is wet-pulverized and / or dispersed to obtain a mixed powder slurry, and the dried powder has a specific surface area of ​​5 m2 as measured by the BET method. 2 / g or more 10m 2 / g or less, (s) wet-pulverizing and / or dispersing the mixed powder slurry so that the average particle size at 50% cumulative frequency in a volume-based particle size distribution measured in accordance with JIS Z8825 by a laser diffraction method is within the range of 0.3 μm to 0.6 μm; (t) preparing a molding powder by drying and sieving the resulting powder obtained by mixing 1 part by mass of the dried powder from the mixed powder slurry with 100 parts by mass of a molding solvent, so that the aggregated powder in the slurry for measuring the aggregated powder average particle size has a cumulative frequency of 50% in a volume-based particle size distribution measured in accordance with JIS Z8825 by a laser diffraction method, within a range of 1 μm or more and 5 μm or less; (u) granulating and molding the molding powder to obtain a molded body; (v) sintering the green body at a temperature in the range of 1250°C to 1600°C to obtain a ZrO2-Y2O3-based zirconia sintered body, the method for producing a zirconia bearing ball comprising the sintered body. Effect of the Invention

[0013] The present invention can provide zirconia media and zirconia bearing balls having improved wear resistance and durability, and methods for producing the same. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a photograph of the medium according to Example 1 taken with a scanning electron microscope (SEM). [Diagram 2] FIG. 2 is a photograph of the medium according to Comparative Example 7 taken with a scanning electron microscope (SEM). [Figure 3A] FIG. 3A is a photograph taken with a scanning electron microscope (SEM) of the media according to Comparative Example 8 before being used in the grinding and / or dispersion treatment. [Figure 3B] FIG. 3B is a scanning electron microscope (SEM) photograph of the media according to Comparative Example 8 after it has been used in the grinding and / or dispersion process. [Figure 4] FIG. 4 is a schematic perspective view showing an example of a bearing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Next, the present invention will be described based on an embodiment, however, the present invention is not limited to the embodiment described below.

[0016] The zirconia media of the present invention satisfies the following requirements (a) to (h), preferably satisfies the following requirement (k), and may also satisfy the following requirement (j), (n) or (o).

[0017] The zirconia bearing ball of the present invention satisfies the following requirements (a) to (h), and further satisfies the following requirements (x) and (y), and preferably satisfies the following requirement (k), and may also satisfy the following requirement (j), (n) or (o).

[0018] The zirconia media or zirconia bearing balls (a) are made of a ZrO2-Y2O3-based zirconia sintered body, and have a Y2O3 / ZrO2 molar ratio in the range of 2.5 / 97.5 to 3.2 / 96.8, (b) an Al2O3 content in the range of 0.1 mass% to 30.0 mass%, (c) contain 90 volume% or more of tetragonal zirconia, (d) have a relative density of 95% or more, (e) have an average crystal grain size in the range of 0.25 μm to 0.50 μm, and (f) are measured at a crosshead speed of 0.5 mm / min. Crushing load The minimum weight is Pmin(N)>600×D 2.0 (D is the average value of the media diameter), (g) the Weibull coefficient of the crushing load value is 10 or more, and (h) the maximum diameter of the media that can be confirmed in an SEM image confirmed using a scanning electron microscope is defined as the media diameter, and the coefficient of variation of the media diameter, derived from the average value and standard deviation of the media diameters of 200 media, is less than 6%. In this specification, in the case of zirconia bearing balls, "media" may be replaced with "bearing balls".

[0019] The zirconia media or zirconia bearing balls are made of a ZrO2-Y2O3 zirconia sintered body, and the chemical composition, crystal phase, relative density, average crystal grain size, minimum value of crushing load, Weibull coefficient of crushing load, and coefficient of variation of media diameter of the sintered body are within a specific range, so that the variation of the shape of the media and the variation of the mechanical properties such as the wear resistance and crushing load of the media can be suppressed. Even when the zirconia media is used as a micro media using a large amount of media in a bead mill rotating at high speed, the media does not crack or chip, and durability and wear resistance can be improved. Since the cracking and chipping of the zirconia media are suppressed, the powder to be treated can be pulverized and dispersed while maintaining the high purity of the powder to be treated. In the case of the zirconia bearing ball, the cracking and chipping of the bearing ball are suppressed, so that a bearing ball that satisfies the specified values ​​described below can be provided.

[0020] The zirconia media or zirconia bearing balls are (a) made of a ZrO2-Y2O3-based zirconia sintered body, and the Y2O3 / ZrO2 molar ratio is in the range of 2.5 / 97.5 to 3.2 / 96.8, and may be in the range of 2.6 / 97.4 to 3.1 / 96.9. When the Y2O3 / ZrO2 molar ratio of the zirconia media or zirconia bearing balls is within the above range, the monoclinic zirconia is small, and the stability of the crystal structure of the tetragonal zirconia is good. When the Y2O3 / ZrO2 molar ratio of the zirconia media or zirconia bearing balls is within the above range, cracking and chipping can be suppressed, and wear resistance and durability can be improved. When the Y2O3 / ZrO2 molar ratio of the zirconia media or zirconia bearing ball is less than 2.5 / 97.5, the content of monoclinic zirconia is high, and the stability of tetragonal zirconia is low. When the Y2O3 / ZrO2 molar ratio of the zirconia media or zirconia bearing ball is less than 2.5 / 97.5, fine cracks are generated by stress, causing breakage and chipping, and the wear resistance or durability is reduced. When the Y2O3 / ZrO2 molar ratio of the zirconia media or zirconia bearing ball is more than 3.2 / 96.8, the amount of tetragonal zirconia is reduced, and the mechanical strength is reduced. When the mechanical strength is reduced, the media will crack or chip in a bead mill under high load, and the wear resistance will be reduced. When the mechanical strength is reduced, the wear resistance and durability of the zirconia bearing ball will be reduced. Since the ZrO2 raw material usually contains a small amount of HfO2, the total amount of ZrO2 and HfO2 is taken as the amount of ZrO2. The ZrO2 powder may contain at least one selected from the group consisting of TiO2, FeO2, MgO, Na2O, and K2O. The content of components other than ZrO2 contained in the ZrO2 powder may be 0.3 mass% or less based on the total amount of ZrO2.

[0021] The zirconia media or zirconia bearing balls have an Al2O3 content of 0.1% by mass or more and 30.0% by mass or less. When the Al2O3 content of the zirconia media or zirconia bearing balls is within the above range, the sinterability of ZrO2 is improved. When the Al2O3 content of the zirconia media or zirconia bearing balls is within the above range, Al2O3 is present as segregation or Al2O3 crystal particles at the grain boundaries of ZrO2, strengthening the grain boundaries of ZrO2 and improving mechanical properties such as impact resistance. When the Al2O3 content of the zirconia media or zirconia bearing balls is less than 0.1% by mass, the effect of improving the sinterability and improving the mechanical properties by adding Al2O3 cannot be obtained. When the Al2O3 content of the zirconia media or zirconia bearing balls exceeds 30.0% by mass, the Al2O3 content increases too much, and the sinterability and mechanical properties are reduced. The Al2O3 content of the zirconia media or zirconia bearing balls is preferably within the range of 0.2 mass % to 25 mass %.

[0022] The zirconia media or zirconia bearing ball preferably contains (k) SiO2 in the range of 0.2% by mass or more and 1.0% by mass or less. When the ZrO2-Y2O3-based zirconia sintered body is used in hot water of 40°C or more, the grain boundaries are easily corroded by water, and the wear resistance may be significantly reduced. When SiO2 is contained in the zirconia media or zirconia bearing ball, the wear resistance can be maintained even when the media is used in hot water of 40°C or more. When the zirconia media or zirconia bearing ball contains SiO2 in the range of 0.2% by mass or more and 1.0% by mass or less, the wear resistance can be maintained by suppressing the water corroding the grain boundaries of ZrO2 in the sintered body constituting the media, even when the media is used in hot water of 40°C or more. When the SiO2 content in the zirconia media or zirconia bearing ball exceeds 1.0% by mass, an SiO2 phase may be formed at the grain boundaries of ZrO2, resulting in a decrease in strength. The SiO2 content in the zirconia media or zirconia bearing balls may be in the range of 0.3% by mass to 0.9% by mass, or in the range of 0.4% by mass to 0.7% by mass. When used under conditions where deterioration does not occur, such as when not used in hot water of 40°C or higher, the zirconia media or zirconia bearing balls may have an SiO2 content of less than 0.2% by mass.

[0023] The zirconia media or zirconia bearing balls contain (c) tetragonal zirconia at 90% by volume or more, preferably at 95% by volume or more. When the zirconia media or zirconia bearing balls contain tetragonal zirconia at 90% by volume or more, mechanical strength such as wear resistance, durability, and impact resistance can be improved. The zirconia media or zirconia bearing balls may contain 100% by volume of tetragonal zirconia. When the zirconia media or zirconia bearing balls contain tetragonal zirconia at less than 90% by volume, monoclinic zirconia is contained in large amounts. Fine cracks are generated around the monoclinic zirconia contained in the zirconia media or zirconia bearing balls, and mechanical strength such as wear resistance, durability, and impact resistance is reduced. The monoclinic zirconia content of the zirconia media or zirconia bearing balls can be up to 5% by volume, and is preferably 5% by volume or less. Furthermore, if the zirconia media or zirconia bearing balls contain a large amount of cubic zirconia, the effect of stress-induced phase transformation decreases, resulting in a decrease in toughness and making the balls more susceptible to microcracks when used in a bead mill under high load. The allowable cubic zirconia content of the zirconia media or zirconia bearing balls is up to 5% by volume, and preferably 5% by volume or less.

[0024] The presence or absence and content of monoclinic zirconia (M), the content of tetragonal zirconia (T), and the presence or absence and content of cubic zirconia (C) in the zirconia crystal phase of the sintered body can be determined by X-ray diffraction. The media is placed in the hardening embedding resin so that it is equal to or larger than the area of ​​a circle with a diameter of 10 mm or more, and the hardening embedding resin is hardened. The media embedded in the hardened hardening embedding resin is ground to about one third of the diameter of the cross section. The ground surface is lapped to a depth of 5 μm or more with 4 to 8 μm diamond abrasive grains, and further with 3 μm or less diamond abrasive grains, and finally polished with 1 μm or less diamond abrasive grains, and mirror-polished so that the surface roughness Rz according to JIS B0601:2001 is less than 0.050 μm (surface roughness Rz<0.05 μm), and measured by X-ray diffraction method at a diffraction angle range of 27 degrees to 34 degrees. The monoclinic zirconia (M) content (volume %) can be calculated from the results obtained by the measurement using the following formula (1). In this specification, the hardening embedding resin can be, for example, a polyester resin, an acrylic resin, or an epoxy resin.

[0025]

number

[0026] The presence or absence and content (volume %) of cubic zirconia (C) can be determined in the same manner as for the content of monoclinic zirconia (M) by measuring the diffraction angle in the range of 70 degrees to 77 degrees by X-ray diffraction, and the content can be calculated from the obtained results using the following formula (2). Furthermore, based on the above results, the content of tetragonal zirconia (T) can be calculated from the following formula (3).

[0027]

number

[0028] The zirconia media or zirconia bearing balls have a relative density (d) of 95% or more, and more preferably 97% or more. When the zirconia media or zirconia bearing balls have a relative density (d) of 95% or more, the zirconia media or zirconia bearing balls have a high relative density. The zirconia media or zirconia bearing balls may have a relative density of 100% or 99.9% or less. The zirconia media or zirconia bearing balls having a high relative density have fewer pores inside the sintered body, and cracks and chipping can be suppressed. When the zirconia media or zirconia bearing balls have a relative density (d) of less than 95%, the sintered body has many pores inside. Zirconia media containing many pores can cause cracks and chipping in a bead mill under high load, and the wear resistance and durability are reduced. The zirconia bearing balls containing many pores have low wear resistance and durability. The relative density of zirconia media or zirconia bearing balls can be calculated from the following formula (4). The apparent density is measured by the gas displacement method specified in JIS R1620. The theoretical density is calculated based on the theoretical density of ZrO2 with Y2O3 dissolved therein (6.1 g / cm 3 ) and the theoretical density of Al2O3 (3.98g / m 3 ) it can be calculated from the composition ratio of ZrO2 and Al2O3 in which Y2O3 is dissolved in the sintered body.

[0029]

number

[0030] Average grain size The zirconia media or zirconia bearing balls have an average crystal grain size (e) in the range of 0.25 μm to 0.50 μm. The zirconia media or zirconia bearing balls may have an average crystal grain size (e) in the range of 0.26 μm to 0.48 μm, or may have an average crystal grain size (e) in the range of 0.3 μm to 0.45 μm. If the zirconia media or zirconia bearing balls have an average crystal grain size (e) of less than 0.25 μm, the toughness is reduced, chipping and cracking are likely to occur in a mill under high load, and it becomes difficult to maintain high purity of the powder to be processed. If the zirconia media or zirconia bearing balls have an average crystal grain size (e) of more than 0.5 μm, the wear resistance and durability are reduced. The wear resistance of the zirconia media or zirconia bearing balls depends on the fine structure of the crystals near the surface of the sintered body constituting the zirconia media or zirconia bearing balls. Therefore, it is preferable to measure the average crystal grain size of the zirconia media or zirconia bearing balls within 10% of the media diameter from the surface of the media toward the center. The average crystal grain size of the zirconia media or zirconia bearing balls can be measured as follows. The sintered body constituting the media is embedded in a hardening type embedding resin, and the hardening type embedding resin is hardened. The sintered body embedded in the hardened hardening type embedding resin is ground from the surface toward the center so that it is less than 10% of the media diameter, and the ground surface is mirror-polished to a surface roughness Rz<0.05μm in accordance with JIS B0601:2001 in the same manner as the measurement surface in which the crystal phase was measured. Next, after thermal etching or chemical etching, it is observed with a scanning electron microscope (SEM) at a magnification where 100 or more crystal grains can be observed in one field of view, and the average crystal grain size can be obtained by the intercept method. Specifically, a straight line of length L is drawn on the surface where the target crystal grains are visible, and the number of crystal grains that this straight line crosses is obtained. The crystal grains that have the end of the straight line inside are counted as 1 / 2. The average crystal grain size can be obtained from the following formula (5). It is preferable to obtain the average crystal grain size by subtracting 2 to 5 of the straight line of length L.

[0031]

number

[0032] For zirconia media or zirconia bearing balls, (f) the minimum crushing load measured at a crosshead speed of 0.5 mm / min is Pmin (N) > 600 × D 2.0 (D is the average media diameter). The minimum crushing load Pmin exceeds the product of the average media diameter D to the power of 2.0 and 600 (Pmin (N)>600×D 2.0 If the above condition is not met, cracks and chips will easily occur in the mill where high loads are applied. The minimum crushing load value Pmin is less than the product of the average media diameter D to the power of 2.0 and 600 (Pmin (N) ≦ 600 × D 2.0 ) indicates that low-strength media with low crushing load values ​​are mixed in. When low-strength media with low crushing load values ​​are mixed in, there is a high probability that the media with low crushing load values ​​will crack or chip due to impact in the mill, where high loads are applied. If zirconia media cracks or chips, it becomes difficult to maintain the high purity of the processed powder. The average media diameter D was calculated by taking the maximum diameter measured from an image of a single piece of media observed using a scanning electron microscope as the media diameter, and averaging the media diameters of 200 pieces of media. The crushing load value is the load value at which one piece of media is broken when it is sandwiched between two diamond sintered bodies or boron nitride (BN) sintered bodies using a material testing machine and a load is applied to the media at a crosshead speed (speed at which the distance between the plates is reduced) of 0.5 mm / min. The crushing load values ​​of 50 pieces of media are measured, and the lowest crushing load value among them is the minimum value Pmin (N).

[0033] The zirconia media or zirconia bearing balls have a Weibull coefficient of (g) the crushing load value of 10 or more, preferably 12 or more. If the Weibull coefficient of (g) the crushing load value of the zirconia media or zirconia bearing balls is 10 or more, the variation in strength is small, and wear resistance and durability can be improved. If the Weibull coefficient of the crushing load value of the zirconia media or zirconia bearing balls is less than 10, the variation in strength becomes large, and the low-strength media will crack or chip in a mill subjected to a high load, resulting in reduced wear resistance and durability. The Weibull coefficient of the crushing load value may be 25 or less. In this specification, the Weibull coefficient is the Weibull coefficient when the crushing load or bending strength of 50 media are Weibull plotted. The Weibull coefficient can be obtained as follows. For the crushing load or bending strength σ of each level i (i = 1 to n), the cumulative fracture probability is obtained from the following formula (6) using the average rank method. When obtaining the Weibull coefficient of bending strength in the following formula (6), the crushing load is replaced with the bending strength. According to the level i of the crushing load or bending strength, a pair of σi and Fi is prepared, and the Y-axis lnln(1-F) is calculated. ―1 , plot lnσ on the X-axis. This Weibull plot (lnln(1-F) -1 The least squares method is applied to the data points (-lnσ) to obtain a linear regression line, and the slope of the line is calculated as the Weibull coefficient m.

[0034]

number

[0035] The zirconia media or zirconia bearing balls preferably have a media diameter of less than 6%, the maximum diameter of the media that can be confirmed in an SEM image confirmed using a scanning electron microscope (h) being the media diameter, and the coefficient of variation of the media diameter derived from the average value and standard deviation of the media diameters of 200 media. The coefficient of variation of the media diameter of the zirconia media or zirconia bearing balls is preferably 5.9% or less, may be 5.8% or less, and more preferably 4% or less. The coefficient of variation of the media diameter is preferably 0%, and may be 0.1% or more. When the coefficient of variation of the media diameter of the zirconia media or zirconia bearing balls (h) is less than 6%, the variation in the media size is small, the grinding characteristics of the media in the bead mill are uniform, and the powder to be processed can be uniformly ground and dispersed. If the coefficient of variation of the (h) media diameter of the zirconia media or zirconia bearing ball is 6% or more, large and small media are mixed, the movement of each size of media is different in the bead mill, the grinding and dispersion characteristics of the media are varied, leading to variation in the particle size distribution of the processed powder, and poor reproducibility in the grinding and dispersion processing. Furthermore, the crushing load value of small media is also small, which causes the media to crack or chip. In addition, since the small media are worn first, the wear is unevenly promoted depending on the media size, which leads to a decrease in wear resistance and durability, which is not preferable. The coefficient of variation of the media diameter can be calculated from the following formula (7).

[0036]

number

[0037] The zirconia quality media or zirconia bearing balls preferably satisfy the above requirements (a) to (h) and further include the above requirement (k). The zirconia quality media or zirconia bearing balls preferably satisfy the above requirements (a) to (h) and further include at least one of the following requirements (j), (k), (n) and (o). The zirconia quality media or zirconia bearing balls preferably satisfy the above requirements (a) to (h) and (k) and further include at least one of the following requirements (j), (n) and (o). The zirconia media or zirconia bearing balls are preferably such that (j) in accordance with ISO 14577, one piece of media is embedded in a hardening embedding resin, the hardening resin is cured, the media is ground to 40 to 50% of its diameter, the ground surface is mirror-polished in the same manner as the measurement surface used to measure the crystalline phase so that the surface roughness is Rz<0.05 μm in accordance with JIS B0601:2001, and the microindentation hardness of the polished media cross section is measured at 10 equally spaced locations using an ultra-microindentation hardness tester, and the coefficient of variation of the microindentation hardness, calculated from the average value and standard deviation of the microindentation hardness measured for the 10 pieces of media, is 5% or less. The zirconia media or zirconia bearing balls preferably have a (k) SiO2 content in the range of 0.2 mass % or more and 1.0 mass % or less. The zirconia media or zirconia bearing balls preferably have a crushing load ratio A (Pmin(N) / Pave(N)) of the minimum crushing load value Pmin(N) to the average crushing load value Pave(N) measured at a crosshead speed of 0.5 mm / min of 0.8 or more. The zirconia media or zirconia bearing balls preferably have a crushing load ratio B (Pave0.1(N) / Pave(N)), where Pave is the average crushing load value measured at a crosshead speed of 0.5 mm / min and Pave0.1(N) is the average crushing load value measured at a crosshead speed of 0.1 mm / min, respectively, of 0.95 or more.

[0038] The zirconia media or zirconia bearing balls are (j) embedded in a hardening resin in accordance with ISO 14577, the hardening resin is hardened, the media is ground to 40% to 50% of its diameter, and the cross section is mirror-polished by the above-mentioned method to a surface roughness Rz<0.05μm in accordance with JIS B0601:2001, and then the microindentation hardness of the polished cross section of the media is measured at 10 equally spaced locations using an ultra-microindentation hardness tester, and the coefficient of variation of the microindentation hardness can be derived from the average value and standard deviation of the microindentation hardness measured for the 10 media. The zirconia media or zirconia bearing balls preferably have (j) a coefficient of variation of the microindentation hardness of 5% or less. The coefficient of variation of the microindentation hardness of the zirconia media or zirconia bearing ball is preferably 4.8% or less, may be 4.5% or less, 4.0% or less, 3.5% or less, preferably 0%, but may be 0.1% or more, 0.2% or more, or 0.5% or more. If the density of a molded body obtained by granulating a molding powder for forming the zirconia media or zirconia bearing ball is non-uniform, the shrinkage amount will differ within one sintered body in the subsequent firing process, and the structure will become more non-uniform. A sintered body obtained by firing a molded body with a large structure non-uniformity will also have non-uniform ultra-microindentation hardness. If the structure is non-uniform, the residual stress will also increase, reducing resistance to impact and causing cracks and chipping when used in a bead mill under high load. If the coefficient of variation of the microindentation hardness of the zirconia media or zirconia bearing ball is 5% or less, the structure within the sintered body constituting the media will be uniform, and cracks and chipping can be suppressed. When the coefficient of variation of the microindentation hardness of zirconia media or zirconia bearing balls exceeds 5%, the structure of the sintered body constituting the media becomes non-uniform. Zirconia media with a non-uniform sintered body structure is prone to cracking and chipping due to collisions between media in a bead mill under high load, and wear resistance is reduced. Zirconia bearing balls with a non-uniform sintered body structure are prone to cracking and chipping when subjected to high load, for example in bearings, and wear resistance and durability are reduced.Even if the media diameter distribution is sharp and the media is spherical, if there is variation in the microindentation hardness inside the media, it will lead to a decrease in impact resistance, wear resistance, and durability. The microindentation hardness of zirconia media or zirconia bearing balls can be measured with a test load of 50 mN, a load application speed of 5 mN / sec, a test load holding time of 1 sec, and an unloading speed of 5 mN / sec. The coefficient of variation of the microindentation hardness of the media measured with an ultra-microindentation hardness tester can be calculated from the following formula (8).

[0039]

number

[0040] The zirconia media or zirconia bearing balls preferably have a media diameter (m) of 0.5 mm or less. The zirconia media or zirconia bearing balls more preferably have a media diameter of 0.2 mm or less. The media diameter may be 0.01 mm or more, or may be 0.015 mm or more. The media diameter measurement method is the same as the measurement method using an image confirmed using a scanning electron microscope. If the zirconia media has a media diameter of 0.5 mm or less, it can be used as a media for pulverizing and dispersing fine powders. For pulverizing and dispersing fine powders, the media must also be very small. To pulverize and disperse fine powders with a size of 1 nm to 100 nm, such as those called nanopowder, it is preferable to use a media diameter of 0.5 mm or less, and it is more preferable to use a micromedia diameter of 0.2 mm or less. If the media size is too large compared to the size of the powder to be processed, the powder cannot be pulverized and dispersed to a minute size. Also, if the media size is too large compared to the size of the powder to be processed, the mass of the media will be large, which will damage the powder surface of the powder to be processed, activating the powder surface and making it more likely to re-agglomerate. If the (m) media diameter of the zirconia bearing ball is small, it can also be used for small bearings.

[0041] The zirconia media or zirconia bearing balls (n) preferably have a crushing load ratio A (Pmin(N) / Pave(N)) of the minimum crushing load value Pmin(N) to the average crushing load value Pave(N) measured at a crosshead speed of 0.5 mm / min of 0.8 or more, and may be 0.81 or more. The crushing load ratio A is 1 or less. The crushing load value is affected by the grain boundary strength of the crystals of the sintered body constituting the media, and the size and number of internal defects. Therefore, if the media has a crushing load ratio A of 0.8 or more, as well as a coefficient of variation indicating the uniformity of the media diameter distribution, then it can be said that the individual media have uniform strength. If the crushing load ratio A of zirconia media or zirconia bearing balls is 0.8 or more, it can be said that they have uniform strength that maintains impact resistance, wear resistance, and durability. The average crushing load value is determined by measuring the crushing load value in the same manner as the minimum crushing load value Pmin (N), and the average crushing load value of 50 media is defined as Pave (N). The crushing load ratio A can be calculated from the following formula (9).

[0042]

number

[0043] The zirconia media or zirconia bearing balls preferably have a crushing load ratio B (Pave0.1(N) / Pave(N)) of the average crushing load value Pave measured at a crosshead speed of 0.5 mm / min to the average crushing load value Pave0.1(N) measured at a crosshead speed of 0.1 mm / min of 0.950 or more, more preferably 0.955 or more, even more preferably 0.960 or more, and even more preferably 0.965 or more. The closer the average crushing load value Pave and the average crushing load value Pave0.1 are to the same value (Pave0.1(N) / Pave(N)=1), the fewer internal defects there are in the zirconia media or zirconia bearing balls. The slower the loading rate, the more likely the stress is to concentrate on structures with low strength, such as non-uniformity and defects within the media, and the lower the crushing load value tends to be. If the crushing load ratio B of the average crushing load value Pave0.1 (N) measured at a crosshead speed of 0.1 mm / min to the average crushing load value Pave (N) measured at a crosshead speed of 0.5 mm / min is 0.95 or more, this indicates that the media has a more uniform strength, and is therefore superior in impact resistance, abrasion resistance, and durability. The average crushing load value Pave0.1 (N) measured at a crosshead speed of 0.1 mm / min is the average crushing load value of 50 media. The crushing load ratio B can be calculated from the following formula (10).

[0044]

number

[0045] Zirconia bearing balls have (x) a fracture toughness of 5.0 MPa m 1 / 2 Above 5.2MPa m 1 / 2 It is preferable that the temperature is 5.4 MPa m or more. 1 / 2 More preferably, it is 5.5 MPa m 1 / 2 More preferably, it is 5.6 MPa m or more. 1 / 2 It is particularly preferable that the temperature is 8.0 MPa m or more. 1 / 2 Less than 7.0MPa m is acceptable. 1 / 2 Less than 6.5MPa m is acceptable. 1 / 2 The zirconia bearing ball may have a fracture toughness of 7.0 MPa m or less. 1 / 2 Less than 6.8MPa m is acceptable. 1 / 2 The (x) fracture toughness of the zirconia bearing ball is 5.0 MPa m 1 / 2 If it is above that, for example, ASTM International (formerly American Society etyIt can meet the fracture toughness of material class III for silicon nitride (Si3N4) bearing balls specified in F2094 of the American Society for Testing and Materials, and can be used as a bearing ball that meets the standard values ​​of ASTM International. It can also meet the fracture toughness of grade 3 for silicon nitride (Si3N4) material for rolling bearing balls specified in JIS R1669, and can be used as a bearing ball that meets the standard values ​​of JIS R1669. The fracture toughness of zirconia bearing balls can be measured in accordance with JIS R1669.

[0046] The fracture toughness of zirconia bearing balls can be measured using the SENB method by pressing the powder for forming zirconia bearing balls into a test molded body, sintering it under the same conditions as the media, and cutting the test piece to dimensions of 3 mm x 4 mm x 45 mm (length x width x thickness) with a #140 diamond wheel. This test piece can be evaluated by three-point bending with a span of 30 mm and a crosshead speed of 0.5 mm / min. A notch can be machined into the center of the tensile surface of the test piece so that the radius of curvature at the tip of the notch is 10 μm and the depth is 1.5 mm, and then the fracture toughness K IC can be calculated from the following equations (11) and (12).

[0047]

number

[0048] The zirconia bearing ball (y) has a bending strength of more than 1100 MPa and a Weibull coefficient of bending strength of more than 7, and may have a bending strength of 1110 MPa or more, 1120 MPa or more, 1150 MPa or more, 1600 MPa or less, 1500 MPa or less, or 1450 MPa or less. The Weibull coefficient of bending strength may be 7.1 or more, 7.5 or more, 8 or more, 30 or less, or 25 or less. If the zirconia bearing ball (y) has a bending strength of more than 1100 MPa and a Weibull coefficient of bending strength of more than 7, it can meet the bending strength of material class III of silicon nitride (Si3N4) bearing balls specified in ASTM International F2094, for example, and can meet the Weibull coefficient of bending strength, and can be used as a bearing ball that meets the standard value of ASTM International. In addition, it meets the bending strength and Weibull coefficient of bending strength of grade 3 of silicon nitride (Si3N4) material for rolling bearing balls specified in JIS R1669, and can be used as a bearing ball that meets the standard values ​​of JIS R1669. The bending strength of zirconia bearing balls can be measured by measuring three-point bending strength of 10 samples at a span of 30 mm and a crosshead speed of 0.5 mm / min in accordance with JIS R1669, and the arithmetic average value of the measured values ​​of the 10 samples can be measured as the bending strength (y). In addition, the Weibull coefficient of bending strength can be calculated by substituting the crushing load value for the bending strength in the above formula (6).

[0049] FIG. 4 is a schematic perspective view showing an example of a bearing using zirconia bearing balls. In the bearing 1, a bearing ball 4 is held in a cage (not shown) between an inner ring 2 and an outer ring 3. Bearings are used in wind power generators, airplanes, automobiles, bicycles, trains, refrigerators, air conditioners, vacuum cleaners, copy machines, washing machines, massage chairs, cameras, electric drivers, personal computers, automatic ticket gates, pedestrian walkways, elevators, conveyors, and other devices, as well as in computer tomography (CT) devices, magnetic resonance imaging (MRI) devices, dental handpieces, and other medical devices. In automobiles, bearings are used in, for example, wheels, suspensions, steering, and the like. In bicycles, bearings are used in, for example, transmissions and wheels. In automatic ticket gates, bearings are used in, for example, roller parts that send tickets, and the like. In dental handpieces, bearings are used in, for example, drills that rotate at high speed.

[0050] Method for producing zirconia media or zirconia bearing balls The method for producing zirconia-based media or zirconia bearing balls of the present invention comprises: (p) mixing a zirconium raw material and a yttrium raw material so that the Y2O3 / ZrO2 molar ratio is within a range of 2.5 / 97.5 to 3.2 / 96.8, hydrolyzing the mixture, and calcining the resulting hydrate of zirconium and yttrium at a temperature within a range of 600°C to 1200°C to obtain a synthetic powder; (q) mixing the Al2O3 powder with the Al2O3 powder so that the Al2O3 content is within the range of 0.1 mass% to 30.0 mass% of the total amount to obtain a mixed powder; (r) The mixed powder is wet-pulverized and / or dispersed to obtain a mixed powder slurry, and the dried powder has a specific surface area of ​​5 m2 as measured by the BET method. 2 / g or more 10m 2 / g or less, (s) wet-pulverizing and / or dispersing the mixed powder slurry so that the average particle size at 50% cumulative frequency in a volume-based particle size distribution measured in accordance with JIS Z8825 by a laser diffraction method is within the range of 0.3 μm to 0.6 μm; (t) preparing a molding powder by drying and sieving the resulting powder obtained by mixing 1 part by mass of the dried powder from the mixed powder slurry with 100 parts by mass of a molding solvent, so that the aggregated powder in the slurry for measuring the aggregated powder average particle size has a cumulative frequency of 50% in a volume-based particle size distribution measured in accordance with JIS Z8825 by a laser diffraction method, within a range of 1 μm or more and 5 μm or less; (u) granulating and molding the molding powder to obtain a molded body; (v) sintering the green body at a temperature in the range of 1250°C to 1600°C to obtain a ZrO2-Y2O3-based zirconia sintered body.

[0051] (p) The zirconium raw material and the yttrium raw material are mixed so that the Y2O3 / ZrO2 molar ratio is within the range of 2.5 / 97.5 to 3.2 / 96.8, hydrolyzed, and the obtained zirconium and yttrium hydrate is calcined within the range of 600°C to 1200°C to obtain a synthetic powder. When the Y2O3 / ZrO2 molar ratio of the synthetic powder is within the range of 2.5 / 97.5 to 3.2 / 96.8, a ZrO2-Y2O3-based zirconia sintered body containing less monoclinic zirconia and 95% or more by volume of tetragonal zirconia can be obtained. When the Y2O3 / ZrO2 molar ratio of the synthetic powder is within the above-mentioned range, the stability of the tetragonal zirconia contained in the obtained sintered body is good, cracking and chipping of the sintered body can be suppressed, and a sintered body with improved wear resistance and durability can be obtained.

[0052] The zirconium raw material and the yttrium raw material are mixed so that the Y2O3 / ZrO2 molar ratio is in the range of 2.5 / 97.5 to 3.2 / 96.8, water is added to form an aqueous solution, and the aqueous solution is hydrolyzed by heating under reflux at a temperature of 100°C. The obtained zirconium and yttrium hydrate is dehydrated, dried, and calcined at a range of 600°C to 1200°C to obtain a synthetic powder. The calcination temperature may be in the range of 800°C to 1000°C. If the calcination temperature is in the range of 600°C to 1200°C, the composition in the synthetic powder becomes uniform, and it is easy to obtain a sintered body with a uniform composition and strength at the time of firing. The calcination time is 30 minutes to 2 hours, and may be 1 hour or less. The calcination is preferably performed in an air atmosphere (oxygen 20% by volume) at standard atmospheric pressure (0.101 MPa).

[0053] In order to prepare the synthetic powder, a zirconium compound is used as a zirconium raw material. Zirconium oxychloride, zirconium acetate, zirconium nitrate, zirconium sulfate, etc. can be used as the zirconium compound. The purity of the zirconium compound is preferably 99.9 mass% or more. If the zirconium compound used as the zirconium raw material contains a large amount of impurities, the impurity phase is likely to be generated at the grain boundaries of the obtained sintered body. If a high load is applied to the sintered body, stress is concentrated in the impurity phase, which is undesirable as it can cause cracking or chipping of the zirconia media made of the sintered body. In this specification, the purity of the zirconium compound can be determined by referring to the value listed in the catalog of each compound.

[0054] For the Y2O3 to be dissolved in ZrO2, an yttrium compound is used as the yttrium raw material. The yttrium compound may be yttrium nitrate, yttrium oxide, or the like. The purity of the yttrium compound is preferably 99.9% by mass or more. If the yttrium compound contains a large amount of impurities, as described above, it is undesirable because the impurity phase is likely to be generated at the grain boundaries of the resulting sintered body.

[0055] (q) A mixed powder is obtained by mixing Al2O3 powder with a synthetic powder so that the content of Al2O3 in the total amount is within the range of 0.1 mass% to 30.0 mass%. When the mixed powder contains Al2O3 powder, the sinterability of a compact made using a molding powder made from the mixed powder is improved. In addition, since Al2O3 segregates to the grain boundaries of ZrO2 and exists as crystal particles of Al2O3, the grain boundaries of ZrO2 are strengthened, and a sintered compact with improved mechanical properties such as impact resistance can be obtained.

[0056] The Al2O3 powder preferably has an aluminum oxide purity of 99.9% by mass or more, and an average particle size at 50% cumulative frequency in the volumetric particle size distribution measured by a laser diffraction method in accordance with JIS Z8825 is in the range of 0.1 μm to 0.3 μm. If the amount of impurities in the Al2O3 powder is large, as described above, an impurity phase is likely to be generated at the grain boundaries of the obtained sintered body. In addition, if the average particle size of the Al2O3 powder is in the range of 0.1 μm to 0.3 μm, the amount of Al2O3 powder that satisfies the requirement (q) is uniformly dispersed in the mixed powder containing the synthetic powder and the Al2O3 powder. In the obtained sintered body, Al2O3 segregates at the grain boundaries of ZrO2 and also exists as Al2O3 crystal particles, and the grain boundaries of ZrO2 are strengthened, resulting in a sintered body with improved mechanical properties such as impact resistance. If the Al2O3 powder exceeds 0.3 μm, the size of the Al2O3 crystal particles relative to the ZrO2 crystal particles becomes too large, making it impossible to make the sintered compact structure uniform.Also, if the Al2O3 powder is below 0.1 μm, it tends to aggregate and cannot be uniformly dispersed.

[0057] The mixed powder preferably contains SiO2 raw material such that SiO2 is in the range of 0.2% by mass to 1.0% by mass relative to the total amount of (w), and may contain SiO2 in the range of 0.3% by mass to 0.9% by mass, or may contain SiO2 in the range of 0.5% by mass to 0.7% by mass. If the mixed powder contains SiO2 raw material such that SiO2 is in the range of 0.2% by mass to 1.0% by mass relative to the total amount of (w), water erosion of the grain boundaries of ZrO2 in the sintered body constituting the media can be suppressed and wear resistance can be maintained even when the media is used in hot water of 40°C or higher.

[0058] The SiO2 raw material may be SiO2 powder such as fumed silica, or silica sol such as ethyl silicate or colloidal silica.

[0059] The powder for molding, which is obtained by drying a mixed powder slurry that has been wet-milled and / or dispersed, has a specific surface area of ​​5 m2 measured by the (r) BET method. 2 / g or more 10m 2 / g or less, and (s) the mixed powder slurry has an average particle size in the range of 0.3 μm or more and 0.6 μm or less, as measured by a laser diffraction method. The resulting mixed powder slurry is dried and sized to have an agglomerated powder particle size as shown below, to obtain a molding powder. The molding powder is used with a specific surface area and average particle shape within the above ranges. When the granulated molded body is sintered, the inside of the molded body is sintered uniformly, and a sintered body having uniform strength can be obtained. When the specific surface area of ​​the mixed powder is 10 m, 2 If the specific surface area of ​​the mixed powder exceeds 5 m / g or the average particle size of the mixed powder is less than 0.3 μm, the sinterability becomes excessively high when the granulated compact is fired, resulting in uneven sintering inside and a sintered compact with weak parts. Stress is likely to concentrate in weak parts in the sintered compact, causing cracks and chips, and reducing wear resistance and durability. 2 If the average particle size of the mixed powder is less than 0.6 μm, the sinterability decreases, defects tend to remain, the strength of the sintered body decreases, cracks and chips occur, and the wear resistance and durability decrease.

[0060] The mixed powder has a specific surface area of ​​5.2 m2 measured by the BET method. 2 / g or more 9.5m 2 The mixed powder may be pulverized and / or dispersed in a wet state so that the average particle size measured by a laser diffraction method is in the range of 0.32 μm to 0.59 μm, or in the range of 0.35 μm to 0.50 μm.

[0061] (t) 1 part by mass of the dried powder from the mixed powder slurry is mixed with 100 parts by mass of a molding solvent, and the resulting slurry is dried and sized so that the aggregated powder in the slurry for measuring the average particle size of the aggregated powder has a cumulative frequency of 50% average particle size of 1 μm or more and 5 μm or less in a volume-based particle size distribution measured by a laser diffraction method in accordance with JIS Z8825. The average particle size of the aggregated powder may be in the range of 1.2 μm or more and 4.9 μm or less, or may be in the range of 1.5 μm or more and 4.0 μm or less. The present inventors have newly discovered that not only the specific surface area and average particle size of the mixed powder, but also the state of the agglomerated powder obtained by drying the mixed powder slurry greatly affects the moldability and sinterability. The state of the aggregated powder obtained by drying the mixed powder slurry has a large effect on the wettability with the molding solvent when the molding powder is granulated. slurryIf the powder for molding is prepared by adjusting the conditions for wet grinding and dispersion, the conditions for adding a suitable surfactant, drying, and granulation so that the average particle size of the dried aggregated powder is in the range of 1 μm to 5 μm, the wettability when the powder for molding is granulated can be suitable, and a molded body with a uniform structure and density can be obtained when granulated. The obtained molded body can be uniformly fired, and the density of the obtained sintered body can be uniform. The surfactant added when the mixed powder is wet ground and dispersed can be a polycarboxylate sodium salt, a polycarboxylate ammonium salt, or the like. The surfactant can be used in the range of 0.1 mass % to 5 mass % with respect to 100 mass % of the mixed powder contained in the mixed powder slurry as necessary. The obtained molded body can be uniformly fired to eliminate the shrinkage difference caused by firing. In this specification, the term "agglomerated powder" refers to a powder in which secondary particles are further weakly agglomerated. Even in a slurry, the agglomerated powder maintains its agglomerated state. The aggregated powder can be mixed in a test tube at a ratio of 1 part by mass of the aggregated powder to 100 parts by mass of the molding solvent to measure the average particle size of the aggregated powder. Specifically, 0.1 g of the aggregated powder and 10 g of the molding solvent are placed in a test tube and heated for 3 seconds. Up and down The slurry is mixed by shaking, sucked up with a dropper, and the slurry sucked up with the dropper is placed in an analytical container, and the slurry in the analytical container is irradiated with laser light to measure the average particle size of the aggregated powder in the slurry. The molding solvent must be the same as the molding solvent used when granulating and molding the molding powder described below to form a molded body. If the average particle size of the aggregated powder is within the range of 1.2 μm to 4.9 μm, it can be used as the molding powder.

[0062] The method for producing zirconia media or zirconia bearing balls includes (u) granulating the obtained molding powder to obtain a molded body. A molding solvent is added to the molding powder, followed by granulation to obtain a molded body. Examples of the molding solvent used during molding include water, alcohols, paraffinic hydrocarbons, and mixtures thereof. Examples of water include ion-exchanged water. Examples of alcohols include alcohols having linear or branched alkyl groups having 1 to 4 carbon atoms. It is preferable to granulate the molded body to obtain a molded body such that the media diameter after sintering is 0.5 mm or less.

[0063] The method for producing zirconia media or zirconia bearing balls includes (v) sintering the obtained molded body at a temperature in the range of 1250°C to 1600°C to obtain a ZrO2-Y2O3-based zirconia sintered body. The sintering temperature is more preferably in the range of 1300°C to 1550°C. When the sintering temperature is in the range of 1250°C to 1600°C, the sintering can be performed uniformly, and a sintered body with high strength can be obtained. The media made of the sintered body obtained by the method for producing zirconia media can satisfy the requirements (a) to (h) above. When the sintering temperature is less than 1250°C, sintering is insufficient, and pores that become defects remain, reducing the strength and reducing the wear resistance of the obtained sintered body. When the sintering temperature exceeds 1600°C, the crystal grain size may become excessively large, and the content of cubic zirconia increases, reducing the toughness and wear resistance. The molded body is preferably fired in a gas furnace or the like in an air atmosphere (oxygen 20% by volume) at standard atmospheric pressure (0.101 MPa).

[0064] The surface of the obtained sintered body is preferably polished using a barrel polishing machine until the surface roughness Rz (maximum height of the roughness curve of the surface roughness) conforming to JIS B0601:2001 is 0.3 μm or less (Rz≦0.3 μm). By polishing the surface of the obtained sintered body with a barrel polishing machine, the surface irregularities are eliminated, and the wear resistance can be improved. The obtained sintered body can be used as a media. EXAMPLES

[0065] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.

[0066] Examples 1 to 8, Comparative Examples 1 to 11 Zirconium oxychloride with a purity of 99.9% by mass (catalog value) and yttrium nitrate with a purity of 99.9% by mass (catalog value) were mixed in water so that the molar ratio of Y2O3 / ZrO2 calculated as oxide was the value shown in Table 2, to obtain an aqueous solution. The aqueous solution was then hydrolyzed under heating and refluxing at 100°C to obtain a precipitate of zirconium hydrate containing yttrium. The zirconium hydrate containing yttrium was dehydrated and dried at 100°C for 24 hours to obtain zirconium hydrate containing yttrium. The zirconium hydrate containing yttrium was calcined in a gas furnace at standard pressure in an air atmosphere for 1 hour after the calcination temperature shown in Table 1 was reached, to obtain a synthetic powder (the treatment (p) above). The obtained synthetic powder was wet-dispersed in water, and mixed with Al2O3 powder having a purity of 99.9 mass% (catalog value) and, if necessary, fumed silica or silica sol having a purity of 99.9 mass% (catalog value) as a SiO2 source so as to obtain the contents shown in Table 2 relative to the total amount (processes (q) and (w) above). The obtained mixed powder was wet-pulverized and / or dispersed using water as a medium to obtain a mixed powder slurry having a specific surface area measured by the BET method described later and an average particle size measured by the laser diffraction method described later, both of which are shown in Table 1. (The above-mentioned treatments (r) and (s)) The mixed powder slurry was dried, and 1 part by mass of the dried powder was mixed with 100 parts by mass of the molding solvent to obtain a slurry for measuring the average particle size of the aggregated powder. The slurry was dried and sized to obtain a molding powder such that the average particle size of the aggregated powder in the slurry was measured by a laser diffraction method described below and had a value shown in Table 1. The sizing was performed by classifying the powder using a sieve (the above-mentioned process (t)).

[0067] Water was added as a molding solvent to each of the molding powders of the Examples and Comparative Examples, and the resulting mixture was granulated to form a molded body, thereby obtaining each of the molded bodies of the Examples and Comparative Examples (the above-mentioned treatment (u)).

[0068] Each of the molded bodies of the Examples and Comparative Examples was sintered in an air atmosphere at standard pressure in a gas furnace for 1 hour after the sintering temperature shown in Table 1 was reached, to obtain sintered bodies of the Examples and Comparative Examples. The surfaces of these sintered bodies were polished using a barrel polishing machine until the surface roughness Rz (maximum height of the roughness curve of the surface roughness) in accordance with JIS B0601:2001 was 0.3 μm or less (Rz≦0.3 μm), and the polished sintered bodies were used as media for grinding and dispersion (treatment (v) above). The roughness curve of the surface roughness was measured using a laser microscope (manufactured by Keyence Corporation).

[0069] The specific surface area and average particle size of each mixed powder in the Examples and Comparative Examples were measured as follows. The average particle size of the aggregated powder of the molding powder was determined as follows. These results are shown in Table 1 together with the calcination temperature and firing temperature of each molded body.

[0070] Specific surface area of ​​mixed powder slurry The specific surface area of ​​the mixed powder slurry was measured by the BET method using a specific surface area measuring device (Tristar II, manufactured by Shimadzu Corporation).

[0071] Average particle size of mixed powder slurry The average particle size of the mixed powder was measured by the laser diffraction method in accordance with JIS Z8825 using a particle size distribution measuring device (MT3000, manufactured by Microtrack Bell Co., Ltd.) to measure the average particle size of the mixed powder at a cumulative frequency of 50% in the volume-based particle size distribution.

[0072] Average particle size of agglomerated powder for molding One part by mass of the dried mixed powder slurry was mixed with 100 parts by mass of ion-exchanged water as a molding solvent to obtain a slurry for measuring the average particle size of the agglomerated powder. The average particle size of the agglomerated powder with a cumulative frequency of 50% in the volume-based particle size distribution of the agglomerated powder in this slurry was measured by the laser diffraction method in accordance with JIS Z8825 using a particle size distribution measuring device (MT3000, manufactured by Microtrack-Bell Corporation).

[0073] The following evaluations were performed on each of the media in the Examples and Comparative Examples, and the results are shown in Tables 2 to 5. For the conditions of each evaluation that are not described below, reference can be made to the conditions of each evaluation described above.

[0074] Average media diameter, coefficient of variation of media diameter For each of the media in the examples and comparative examples, images of 200 media were taken using a scanning electron microscope (SEM) (SU3500, manufactured by Hitachi High-Tech Corporation). The maximum diameter of the media was taken as the media diameter and the particle size distribution of the media diameters of the 200 media was created using image analysis software (Image-Pro Plus, manufactured by Nippon Roper Co., Ltd.). The average value and standard deviation of the media diameters of the 200 media were calculated, and the coefficient of variation of the media diameter was calculated based on the above formula (7).

[0075] Crystalline phase content of media (volume %) For each of the media in the examples and comparative examples, the media made of the sintered body was placed in the hardening type embedding resin so that the area was equal to or larger than the area of ​​a circle with a diameter of 10 mm or more. The hardening type embedding resin (epoxy resin) was hardened, and the media made of the sintered body embedded in the hardening type embedding resin was ground to about one third of the diameter of the cross section, and the ground surface was mirror-polished by the above-mentioned method so that the surface roughness was Rz<0.05 μm according to JIS B0601:2001. The diffraction angle was measured by X-ray diffraction method in the range of 27 degrees to 34 degrees and in the range of 70 degrees to 77 degrees. From the obtained results, the monoclinic zirconia (M) content (volume %), tetragonal zirconia (T) content (volume %), and cubic zirconia (C) content (volume %) were calculated based on the above formulas (1) to (3). The conditions for X-ray diffraction were as follows: X-ray source: CuKα, output: 40 kV / 40 mA, incident side divergence slit: 1 / 2°, incident side Soller slit: 4.1°, receiving side divergence slit: 5.2 mm, receiving side Soller slit: OPEN, scan speed: 0.5° / min, scan axis 2θ / θ.

[0076] Relative Density For each of the media in the examples and comparative examples, the apparent density was measured based on the gas displacement method defined in JIS R1620. Furthermore, the theoretical density of each media was calculated from the Y2O3 / ZrO2 molar ratio and the Al2O3 content, and the relative density (%) was calculated based on the above formula (4). The theoretical density was calculated based on the theoretical density of ZrO2 in which Y2O3 is dissolved (6.1 g / cm 3 ) and the theoretical density of Al2O3 (3.98g / m 3 ) and calculated from the composition ratio of ZrO2 and Al2O3 in which Y2O3 is dissolved in the sintered body.

[0077] Average grain size For each of the media in the examples and comparative examples, the media was embedded in a hardening type embedding resin (epoxy resin), and the hardening type embedding resin was hardened. The media embedded in the hardening type embedding resin was ground from the surface toward the center to less than 100 μm, and the ground surface was polished to a mirror surface by the above-mentioned method, and then thermal etching or chemical etching was performed. After that, the media was observed with a scanning electron microscope (SEM) (SU3500, manufactured by Hitachi High-Tech Corporation) at a magnification where 100 or more crystal grains could be observed in one field of view, and the average crystal grain size was obtained by the intercept method. Specifically, 10 straight lines of length L were drawn on the surface where the target crystal grains were visible, and the number of crystal grains that were crossed by these straight lines was calculated, and the crystal grains with the ends of the straight lines inside were counted as 1 / 2, and the average crystal grain size was calculated based on the above formula (5).

[0078] Minimum crushing load value Pmin (N), 600 x D 2.0 For each medium in the Examples and Comparative Examples, a universal material testing machine (5965, Instron Corp.) was used, and a boron nitride (BN) sintered body was used as the pressure plate. One medium was sandwiched between two pressure plates, and a load was applied at a crosshead speed of 0.5 mm / min. The pressure at which the medium broke was measured as the crushing load value. The average crushing load value of 50 media was defined as Pave (N), and the minimum crushing load value of 50 media was defined as Pmin (N). In addition, the difference between 600 and D was calculated from the average media diameter (D). 2.0 Calculate the product and set it to the specified value (600 x D 2.0 ) was decided.

[0079] Weibull coefficient of crushing load For each media of the examples and comparative examples, the crushing load values ​​of 50 media were plotted in the same manner as in the measurement of the minimum crushing load value, and the cumulative fracture probability was calculated from the above formula (6) using the average rank method for the crushing load value σ of each level i (i = 1 to n). According to the level i of the crushing load value, a pair of σi and Fi was set up, and the Y axis was expressed as lnln(1-F) ―1 , the x-axis is plotted as lnσ. This Weibull plot (lnln(1-F) -1The least squares method was applied to the data points of (-lnσ) to obtain a linear regression line, and the slope of the line was calculated as the Weibull coefficient.

[0080] Crushing load ratio A For each of the media in the Examples and Comparative Examples, in the same manner as in measuring the minimum crushing load value, the crushing load ratio A (Pmin(N) / Pave(N)) of the minimum crushing load value Pmin(N) to the average crushing load value Pave(N) measured for 50 media at a crosshead speed of 0.5 mm / min was calculated based on the above formula (9).

[0081] Crushing load ratio B For each of the media in the Examples and Comparative Examples, in the same manner as in measuring the minimum crushing load value, the crushing load ratio B (Pave0.1(N) / Pave(N)), where Pave is the average crushing load value Pave measured at a crosshead speed of 0.5 mm / min for 50 media, and Pave0.1(N) is the average crushing load value measured at a crosshead speed of 0.1 mm / min, was calculated based on the above formula (10).

[0082] Coefficient of variation of hardness measured with an ultra-microindentation hardness tester For each of the media in the examples and comparative examples, one media was embedded in a hardening type embedding resin (epoxy resin), and the hardening type embedding resin was hardened. The media was ground to 40% to 50% of its diameter, and the cross section was mirror-polished by the above-mentioned method to a surface roughness Rz<0.05 μm in accordance with JIS B0601:2001. Thereafter, the micro-embedding hardness (N / mm) was measured at 10 equally spaced points in the diametric direction of the cross section of the media using a Berkovich type indenter with a load of 50 mN, a load application speed of 5 mN / sec, a test load holding time of 1 sec, and an unloading speed of 5 mN / sec. 2 The coefficient of variation of the ultra-microindentation hardness was calculated based on the average value and standard deviation of the micro-embedding hardness measured for the 10 media, according to the above formula (8).

[0083] Flexural strength and Weibull modulus of flexural strength Preparation of samples for processing Each molding powder of the Examples and Comparative Examples was subjected to a compression test at 1000 kgf / cm using a Sr.CIP-M manufactured by Kobe Steel, Ltd. 2 The sample was then sintered under the same conditions as the media to prepare a processing sample. The processing sample was then ground with a #140 diamond wheel to a size of 3 mm length x 4 mm width x 45 mm thickness to prepare a test piece. Flexural strength and Weibull modulus of flexural strength In accordance with JIS R1601, the three-point bending strength was measured for 10 test piece samples at a span of 30 mm and a crosshead speed of 0.5 mm / min, and the arithmetic average value was taken as the bending strength. For each of the media in the examples and comparative examples, the Weibull coefficient of bending strength was determined based on the above-mentioned formula (6).

[0084] Fracture toughness The bending strength was evaluated by the SENB method using a test piece similar to that used to measure bending strength, with a span of 30 mm and a crosshead speed of 0.5 mm / min. A notch was machined in the center of the tensile surface of the test piece, with a radius of curvature of the tip of the notch of 10 μm and a depth of 1.5 mm. The fracture toughness was calculated based on the above-mentioned formulas (11) and (12), as the fracture toughness (K IC ) was sought.

[0085] Distributed Processing Using the media of the examples and comparative examples, a dual apex mill (DAM-015, manufactured by Hiroshima Metal & Machinery Co., Ltd.) was used, the mill member vessel was ZTA (alumina zirconia composite material), the rotor was UHMV (made of polyethylene), the media filling amount was 60 volume % of the mill volume, and the rotor peripheral speed was 8 m / s, and the dispersion treatment of the treated powder was performed under the following conditions. The temperature of the first test slurry was 40°C or less or a temperature exceeding 40°C. For Example 8, the temperature of the first test slurry was both 40°C or less and a temperature exceeding 40°C. Powder to be treated: Titanium oxide (primary particle diameter measured from a transmission electron microscope (TEM) image: 35 nm (catalog value), specific surface area measured by the BET method: 37 m 2 / g (catalog value) First test slurry concentration: 10% by mass First test slurry flow rate: 160 mL / min Dispersion time: 3 hours

[0086] Calcium carbonate (CaCO3) grinding and dispersion processing Using the media of Examples 2 and 7 and the media of Comparative Examples 6 and 8, a Dual Apex Mill (DAM-015, manufactured by Hiroshima Metal & Machinery Co., Ltd.) was used, the mill member vessel was ZTA (alumina-zirconia composite material), the rotor was UHMV (made of polyethylene), the media filling amount was 60 volume % of the mill volume, the rotor peripheral speed was 8 m / s, and the powder to be treated was mixed with water under the following conditions to prepare a second test slurry, which was then subjected to dispersion treatment. The temperature of the dispersion treatment is shown in Table 5. Powder to be treated: Calcium carbonate (average particle size measured by laser diffraction particle size distribution measurement method: 2.1 μm (catalog value), specific surface area measured by BET method: 10 m 2 / g (catalog value) Slurry concentration for second test: 10% by mass Slurry flow rate for second test: 160mL / min Dispersion time: 3 hours

[0087] Wear rate After the dispersion treatment, the amount of ZrO2 (mass ppm / hour) contained in the first test slurry or the second test slurry as media wear powder was measured from the treated powder (titanium oxide powder and calcium carbonate powder) after the dispersion treatment by high-frequency inductively coupled plasma optical emission spectrometry (ICP) using an ICP optical emission analyzer (ICPS-8100, manufactured by Shimadzu Corporation). The wear rate (mass ppm / hour) measured for the amount of ZrO2 in the treated powder (titanium oxide) after the dispersion treatment is shown in Table 4. In addition, the wear rate (mass ppm / hour) measured for the amount of ZrO2 in the treated powder (calcium carbonate powder) after the dispersion treatment is shown in Table 5. The wear rate was calculated by the following formula (13).

[0088]

number

[0089] Whether the media is cracked or not For the media before and after dispersion treatment, 10% of the media used was taken out, and images were visually observed at 200x magnification using a digital microscope (VHX-6000, Keyence Corporation). The presence or absence of cracks in the media after dispersion treatment of the treated powder (titanium oxide powder) is shown in Table 4, and the presence or absence of cracks in the media after dispersion treatment of the treated powder (calcium carbonate powder) is shown in Table 5.

[0090] [Table 1]

[0091] [Table 2]

[0092] [Table 3]

[0093] [Table 4]

[0094] [Table 5]

[0095] The media of Examples 1 to 8 met all the requirements (a) to (h), (j), (k), (n) and (o) described above, and also met the treatments (p) to (w) described above in the manufacturing method. The media of Examples 1 to 8 also met the requirements (x) and (y) described above, and for example, met the fracture toughness, bending strength and Weibull coefficient of bending strength required for material class III of silicon nitride (Si3N4) bearing balls specified in F2094 of ASTM International or grade 3 of rolling bearing silicon nitride (Si3N4) material specified in JIS R1669. The media of Examples 1 to 5 and Example 8 had excellent wear resistance, with a wear rate of less than 100 mass ppm / hour, when used in the grinding and dispersing treatment of the first test slurry containing the powder to be treated using a medium (water) at a temperature of 40°C or less. Furthermore, the media of Examples 6 and 7 had a wear rate of 101 mass ppm / hour or less when used in the grinding and dispersion treatment of the first test slurry containing the powder to be treated (titanium oxide powder) with a small primary particle size using a medium (water) with a temperature exceeding 40°C, and had excellent wear resistance even when used in warm water. The media of Examples 1 to 7 had excellent durability with no cracks or chips even after the grinding and dispersion treatment.

[0096] The media of Examples 2 and 7, when used in the pulverization and dispersion treatment of the second test slurry containing the powder to be treated (calcium carbonate) having an average particle size of 1 μm to 10 μm, had an abrasion rate of 1.5 mass ppm / hour or less, and were excellent in abrasion resistance. From this result, it was confirmed that the media that satisfy the above-mentioned requirements (a) to (h), and preferably the requirements (j), (k), (n) and (o), are excellent in abrasion resistance even in the pulverization and dispersion treatment of calcium carbonate used as a pharmaceutical powder, and can pulverize and disperse the powder to be treated while maintaining the purity of the powder to be treated at a high level without cracking or chipping. Figure 1 is a photograph of the media of Example 1 taken with a scanning electron microscope (SEM). The media of Example 1 is nearly spherical and has excellent abrasion resistance.

[0097] The media of Comparative Example 1 has a Y2O3 / ZrO2 molar ratio of less than 2.5 / 97.5 and a tetragonal zirconia content of less than 90 volume %, and does not satisfy the requirements (a) and (c). 1 / 2 and a bending strength of 770 MPa, which does not satisfy some of the requirements (x) and (y). The media of Comparative Example 1 does not satisfy the treatment of (p) in the manufacturing method either. The media of Comparative Example 1 has a high monoclinic zirconia content of 11 volume %, which results in poor mechanical properties and reduced wear resistance. The media of Comparative Example 1 also has a crushing load ratio B which does not satisfy the requirement (o).

[0098] The media of Comparative Examples 2 and 3 do not have an Al2O3 content within the range of 0.1 mass% or more and 30.0 mass% or less, and do not satisfy the requirement (b) above. The media of Comparative Example 2 does not contain Al2O3, so the sinterability is not improved and the relative density is less than 95%, and does not satisfy the requirement (d) above. Since the mechanical properties are not improved, the minimum crushing load value Pmin (N) is greater than 600×D. 2.0 The media of Comparative Example 2 does not satisfy the requirement (f) above. The Weibull coefficient of the crushing load value is also less than 10, so it does not satisfy the requirement (g). The media of Comparative Example 2 has a bending strength of 700 MPa, so it does not satisfy part of the requirement (y). The media of Comparative Example 2 includes media with low strength, so stress is concentrated on the media with low strength, which makes them prone to cracking and chipping, and reduces wear resistance and durability. The media of Comparative Example 3 has a relative density of less than 95%, so it does not satisfy the requirement (d) above, and many internal defects remain. The media of Comparative Example 3 does not have improved mechanical properties, so it does not satisfy the minimum crushing load value Pmin(N)>600×D 2.0 The media of Comparative Example 3 does not satisfy the above requirement (f), and thus has reduced wear resistance and durability. The coefficient of variation of the microindentation hardness measured using an ultra-microindentation hardness tester also exceeds 5%, and the media of Comparative Example 3 has a fracture toughness of 4.8 MPa m 1 / 2and the bending strength was 690 MPa, which does not satisfy a part of the requirements (x) and (y). When hot water of 40°C was used in the grinding and dispersion treatment, the wear resistance of the media of Comparative Example 3 further decreased.

[0099] The media in Comparative Examples 4 and 5 have a specific surface area of ​​5 m 2 / g or more 10m 2 / g or less. In addition, the media of Comparative Examples 4 and 5 do not satisfy the treatment of (p) above, since the calcination temperature when obtaining the synthetic powder is not within the range of 600°C or more and 1200°C or less. In the media of Comparative Example 4, the mixed powder has a large specific surface area and is a fine powder, so the sintering is non-uniform and the Weibull coefficient of the crushing load value is less than 10, and the media does not satisfy the requirement (g). In low-strength media, stress is concentrated in low-strength parts inside the media, reducing wear resistance and durability. The media of Comparative Example 4 had a coefficient of variation of hardness measured using an ultra-microindentation hardness tester that exceeded 5%, and the crushing load ratio A was less than 0.8, failing to satisfy the requirements (j) and (n) above. The media of Comparative Example 5 has a small specific surface area and low sinterability, so defects remain inside the sintered body and the relative density is less than 95%, and does not satisfy the requirement (d) above. The media of Comparative Example 5 has a minimum crushing load value Pmin (N)>600×D 2.0 The medium of Comparative Example 5 had a bending strength of 750 MPa and a Weibull modulus of bending strength of 5.6, which does not satisfy the requirement (y) above. The media of Comparative Examples 4 and 5 show a further decrease in wear resistance when hot water exceeding 40° C. is used in the grinding and dispersion treatment.

[0100] The media of Comparative Examples 6 and 7 do not satisfy the treatment (t) above, which is to make the average particle diameter of the aggregated powder obtained by drying the mixed powder slurry 1 μm or more and 5 μm or less. The media of Comparative Example 6 has an average particle diameter of the mixed powder of less than 0.3 μm, and does not satisfy the treatment (s) above. The media of Comparative Example 7 has a SiO2 content of more than 1.0 mass%, and does not satisfy the requirement of (k) or (w). The media of Comparative Examples 6 and 7 have an average particle diameter of the aggregated powder that is not in the range of 1 μm or more and 5 μm or less, and therefore have poor moldability, a coefficient of variation of the media diameter of 6% or more, and do not satisfy the requirement of (h), and the particle size distribution of the media diameter is uneven, and stress is concentrated in the low-strength media, cracks and chips occur, and the wear resistance and durability are reduced. The media of Comparative Example 6 had a minimum crushing load value Pmin (N)>600×D 2.0 The Weibull coefficient of the crushing load value and the crushing load ratio A do not satisfy the requirements of (g) and (n) above. The media of Comparative Example 6 has a bending strength of 1080 MPa, which does not satisfy part of the requirement of (y) above. The media of Comparative Example 7 has an SiO2 content exceeding 1.0 mass %, and a second phase consisting of an SiO2 phase is formed at the grain boundaries of ZrO2. The minimum crushing load value Pmin (N) is greater than 600×D. 2.0 The media of Comparative Example 7 did not satisfy the requirement (f) above, and the crushing load ratio A and the crushing load ratio B did not satisfy the requirements (n) and (o) above. The media of Comparative Example 7 had a Weibull modulus of bending strength of 6.2, which does not satisfy part of the requirement (y). In the media of Comparative Example 7, since the inside of the molded body was non-uniform, firing shrinkage proceeded non-uniformly, and it was confirmed that there were irregularly shaped sintered bodies as shown in Fig. 2. Fig. 2 is a photograph of the media of Comparative Example 7 taken with a scanning electron microscope (SEM). Media containing such irregularly shaped sintered bodies are subjected to non-uniform loads during dispersion treatment, which makes them prone to cracking and chipping, reducing wear resistance and durability, and cracking and chipping were confirmed in the media after use.

[0101] The media of Comparative Example 8 has a Y2O3 / ZrO2 molar ratio exceeding 3.2 / 96.8, and does not satisfy the requirement (a) above. The media of Comparative Example 8 has a high content of cubic zirconia (C) of 6 volume %, which leads to a decrease in toughness, and the low-strength media is prone to cracking and chipping, and the wear resistance and durability are reduced. The media of Comparative Example 8 has a minimum crushing load value Pmin (N)>600×D 2.0 (requirement (f) above), and the crushing load ratio A and the crushing load ratio B do not satisfy the requirements (n) and (o) above. The media of Comparative Example 8 has a bending strength of 980 MPa, which does not satisfy part of the requirement (y) above. It was confirmed that the media of Comparative Example 8 had low strength parts and had cracked sintered bodies as shown in FIG. 3A. FIG. 3A is a scanning electron microscope (SEM) photograph of the media of Comparative Example 8 before it was used in the crushing and / or dispersion treatment. The media containing the cracked sintered bodies was subjected to an uneven load during the dispersion treatment, and after it was used in the dispersion treatment, it was confirmed that the sintered bodies were broken into pieces as shown in FIG. 3B. FIG. 3B is a scanning electron microscope (SEM) photograph of the media of Comparative Example 8 after it was used in the crushing and / or dispersion treatment.

[0102] The media of Comparative Examples 9 and 10 had firing temperatures outside the range of 1250° C. or higher and 1600° C. or lower, and did not satisfy the treatment (v) above. The media of Comparative Example 9 has a firing temperature exceeding 1600°C, and the crystal grain size is excessively large, with the average crystal grain size exceeding 0.5 μm, and does not satisfy the requirement (e). The media of Comparative Example 9 has a tetragonal zirconia content of less than 90 volume %, and does not satisfy the requirement (c). The media of Comparative Example 9 has a cubic zirconia (C) content of 11 volume %, which is high, leading to a decrease in toughness, and the low-strength media is prone to cracking and chipping, and the wear resistance and durability are reduced. The media of Comparative Example 9 also has a coefficient of variation of ultra-microindentation hardness that is large by more than 5%, and the crushing load ratio B is less than 0.95, and does not satisfy the requirements (j) and (o). The media of Comparative Example 9 has a bending strength of 910 MPa, and does not satisfy some of the requirements (y). The media of Comparative Example 10 is sintered at a temperature lower than 1250°C, and does not meet the treatment (v) above. The media of Comparative Example 10 has impurities due to sintering, and defects remain, reducing strength, wear resistance, and durability. The media of Comparative Example 10 has a relative density of 90% or less, an average crystal grain size of less than 0.25 μm, and a Weibull coefficient of the crushing load value of less than 10, and does not meet the requirements of (d), (e), and (g) above. The media of Comparative Example 10 has a minimum crushing load value Pmin(N)>600×D 2.0 The media of Comparative Example 10 does not satisfy the fracture toughness of 4.9 MPa m 1 / 2 and the bending strength is 720 MPa, which does not satisfy some of the requirements (x) and (y).

[0103] The media of Comparative Example 11 had a minimum crushing load value Pmin (N)>600×D 2.0 The media of Comparative Example 11 does not satisfy the requirement (f) above. The crushing load ratio A and the crushing load ratio B also do not satisfy the requirements (n) and (o) above. The media of Comparative Example 11 has a SiO2 content of more than 1.0 mass%, and does not satisfy the requirement (k) above. The media of Comparative Example 11 has a fracture toughness of 4.8 MPa m 1 / 2and a bending strength of 1030 MPa, which does not satisfy some of the requirements (x) and (y). The media of Comparative Example 11 has an SiO2 content of more than 1.0 mass%, so a second phase consisting of an SiO2 phase is formed at the grain boundaries of ZrO2, causing cracks and chips, and reducing the wear resistance and durability. The wear resistance of the media of Comparative Example 11 is further reduced when hot water exceeding 40°C is used in the grinding and dispersion treatment.

[0104] The media in Comparative Example 12 has a specific surface area of ​​10 m 2 / g, so it does not satisfy the treatment of (r) above. The media of Comparative Example 12 has too high a sinterability, so the structure is not sintered uniformly, the variation coefficient of the ultramicroindentation hardness exceeds 5%, and it does not satisfy the requirement of (j) above. Furthermore, the crushing load ratio A of the media of Comparative Example 12 does not satisfy the requirement of (n) above. The Weibull coefficient of the crushing load of the media of Comparative Example 12 does not satisfy the requirement of (g) above. The Weibull coefficient of the bending strength of the media of Comparative Example 12 is 5.8, so it does not satisfy part of the requirement of (y) above. The strength of the media of Comparative Example 12 is not uniform, so stress is concentrated in the media with low strength, and the wear resistance is reduced. [Industrial Applicability]

[0105] The zirconia media according to the present disclosure can suppress cracking and chipping, have excellent wear resistance and durability, and maintain the high purity of the powder to be processed, even when used under high load in a bead mill rotating at high speed. The zirconia media according to the present disclosure has no variation in sintering characteristics and high mechanical properties, so it can be fully used not only for powders used in electronic component materials, but also as a medium for grinding and dispersing pharmaceutical powders that need to maintain high purity. In addition, it has high mechanical properties and little variation in shape, and satisfies the fracture toughness, bending strength, and Weibull coefficient of bending strength required for, for example, silicon nitride (Si3N4) bearing ball material class III specified in ASTM International F2094 or rolling bearing silicon nitride (Si3N4) material grade 3 specified in JIS R1669, so it can be fully used as a bearing ball. Bearings equipped with zirconia bearing balls can be used in wind turbines, airplanes, automobiles, bicycles, trains, refrigerators, air conditioners, vacuum cleaners, copy machines, washing machines, massage chairs, cameras, electric screwdrivers, personal computers, automatic ticket gates, pedestrian walkways, elevators, conveyors, as well as in computed tomography (CT) devices, magnetic resonance imaging (MRI) devices, dental handpieces, and other medical equipment. [Explanation of symbols]

[0106] 1: bearing, 2: inner ring, 3: outer ring, 4: bearing ball.

Claims

1. (a) ZrO 2 -Y 2 O 3 The sintered body is made of zirconia. 2 O 3 / ZrO 2 The molar ratio is within the range of 2.5 / 97.5 to 3.2 / 96.8, (b) Al 2 O 3 The content is in the range of 0.1 mass% or more and 30.0 mass% or less, (c) containing 90% by volume or more of tetragonal zirconia; (d) the relative density is 95% or more; (e) the average crystal grain size is in the range of 0.25 μm or more and 0.50 μm or less; (f) The minimum crushing load measured at a crosshead speed of 0.5 mm / min is Pmin (N)>600×D 2.0 (D is the average media diameter) (g) The Weibull coefficient of the crushing load value is 10 or more; (h) the maximum diameter of the media that can be confirmed in an SEM image confirmed using a scanning electron microscope is defined as the media diameter, and the coefficient of variation of the media diameter derived from the average value and standard deviation of the media diameters of 200 media is less than 6%; A zirconia-based media satisfying the above requirements (a) to (h).

2. (j) The zirconia-based media according to claim 1, wherein in accordance with ISO 14577, one piece of media is embedded in a hardening type embedding resin, the hardening type embedding resin is hardened, the media is ground to 40 to 50% of its diameter, the cross section is mirror-polished, and the hardness of the polished cross section of the media is measured at 10 equally spaced locations using an ultra-microindentation hardness tester, and the coefficient of variation of the microindentation hardness derived from the average value and standard deviation of the microindentation hardness measured for the 10 pieces of media is 5% or less.

3. (k) SiO 2 The zirconia-based media according to claim 1 or 2, wherein the content is within the range of 0.2 mass % or more and 1.0 mass % or less.

4. (n) The zirconia-based media according to claim 1 or 2, wherein the crushing load ratio A (Pmin(N) / Pave(N)) of the minimum crushing load value Pmin(N) to the average crushing load value Pave(N) measured at a crosshead speed of 0.5 mm / min is 0.8 or more.

5. (o) The zirconia-based media according to claim 1 or 2, wherein the crushing load ratio B (Pave0.1(N) / Pave(N)) of the average crushing load values ​​Pave measured at a crosshead speed of 0.5 mm / min to the average crushing load values ​​Pave0.1(N) measured at a crosshead speed of 0.1 mm / min is 0.95 or more.

6. (a) ZrO 2 -Y 2 O 3 The sintered body is made of zirconia. 2 O 3 / ZrO 2 The molar ratio is within the range of 2.5 / 97.5 to 3.2 / 96.8, (b) Al 2 O 3 The content is in the range of 0.1 mass% or more and 30.0 mass% or less, (c) containing 90% by volume or more of tetragonal zirconia; (d) the relative density is 95% or more; (e) the average crystal grain size is in the range of 0.25 μm or more and 0.50 μm or less; (f) The minimum crushing load measured at a crosshead speed of 0.5 mm / min is Pmin (N)>600×D 2.0 (D is the average media diameter) (g) The Weibull coefficient of the crushing load value is 10 or more; (h) the maximum diameter of the media that can be confirmed in an SEM image confirmed using a scanning electron microscope is defined as the media diameter, and the coefficient of variation of the media diameter derived from the average value and standard deviation of the media diameters of 200 media is less than 6%; (x) Fracture toughness of 5.0 MPa m 1/2 Beyond (y) A zirconia bearing ball having a bending strength exceeding 1100 MPa and a Weibull modulus of bending strength exceeding 7.

7. (p) Y 2 O 3 / ZrO 2 A synthetic powder obtained by mixing a zirconium raw material and a yttrium raw material so that the molar ratio is within a range of 2.5 / 97.5 to 3.2 / 96.8, hydrolyzing the mixture, and calcining the resulting hydrate of zirconium and yttrium at a temperature within a range of 600° C. to 1200° C.; (q) Al relative to the total amount 2 O 3 The content of Al is in the range of 0.1 mass % to 30.0 mass %. 2 O 3 and mixing the powder to obtain a mixed powder. (r) The mixed powder is wet-pulverized and / or dispersed to obtain a mixed powder slurry, and the dried powder has a specific surface area of ​​5 m2 or less as measured by the BET method. 2 / g or more 10m 2 / g or less, (s) wet-pulverizing and / or dispersing the mixed powder slurry so that the average particle size at 50% cumulative frequency in a volume-based particle size distribution measured by a laser diffraction method in accordance with JIS Z8825 is in the range of 0.3 μm to 0.6 μm; (t) preparing a molding powder by drying and sieving the resulting powder, which is obtained by mixing 1 part by mass of the dried powder obtained from the mixed powder slurry with 100 parts by mass of a molding solvent, so that the aggregated powder in the slurry for measuring the aggregated powder average particle size has a cumulative frequency of 50% in a volume-based particle size distribution measured in accordance with JIS Z8825 by a laser diffraction method, within a range of 1 μm or more and 5 μm or less; (u) granulating and molding the molding powder to obtain a molded body; (v) sintering the molded body at a temperature in the range of 1250° C. to 1600° C. to obtain ZrO 2 -Y 2 O 3 A method for producing a zirconia-based media comprising obtaining a zirconia-based sintered body, the method comprising the steps of:

8. The mixed powder contains (w) SiO 2 The content of SiO is in the range of 0.2 mass% or more and 1.0 mass% or less. 2 The method for producing zirconia media according to claim 7, which comprises the step of:

9. (p) Y 2 O 3 / ZrO 2 A synthetic powder obtained by mixing a zirconium raw material and a yttrium raw material so that the molar ratio is within a range of 2.5 / 97.5 to 3.2 / 96.8, hydrolyzing the mixture, and calcining the resulting hydrate of zirconium and yttrium at a temperature within a range of 600° C. to 1200° C.; (q) Al relative to the total amount 2 O 3 The content of Al is in the range of 0.1 mass % to 30.0 mass %. 2 O 3 and mixing the powder to obtain a mixed powder. (r) The mixed powder is wet-pulverized and / or dispersed to obtain a mixed powder slurry, and the dried powder has a specific surface area of ​​5 m2 or less as measured by the BET method. 2 / g or more 10m 2 / g or less, (s) wet-pulverizing and / or dispersing the mixed powder slurry so that the average particle size at 50% cumulative frequency in a volume-based particle size distribution measured by a laser diffraction method in accordance with JIS Z8825 is in the range of 0.3 μm to 0.6 μm; (t) preparing a molding powder by drying and sieving the resulting powder, which is obtained by mixing 1 part by mass of the dried powder obtained from the mixed powder slurry with 100 parts by mass of a molding solvent, so that the aggregated powder in the slurry for measuring the aggregated powder average particle size has a cumulative frequency of 50% in a volume-based particle size distribution measured in accordance with JIS Z8825 by a laser diffraction method, within a range of 1 μm or more and 5 μm or less; (u) granulating and molding the molding powder to obtain a molded body; (v) sintering the molded body at a temperature in the range of 1250° C. to 1600° C. to obtain ZrO 2 -Y 2 O 3 4. A method for producing a zirconia bearing ball comprising the steps of: obtaining a zirconia-based sintered body; and

10. The mixed powder contains (w) SiO 2 The content of SiO is in the range of 0.2 mass% or more and 1.0 mass% or less. 2 The method for producing a zirconia bearing ball according to claim 9, further comprising the step of:

Citation Information

Patent Citations

  • Member for crushing machine

    JP1994015191A

  • Zirconia ball and its production

    JP1994183833A

  • Method for dispersing pigment

    JP1995155577A

  • Zirconia-based sintered compact, production of the same and material for crushing part

    JP1997188562A

  • Crusher, member for crusher, crushing medium, composite ceramics sintered compact an crushing method

    JP1998085619A

Cited By

  • Zirconia-based media and method for manufacturing the same

    JP2025083366A